Optimalisasi Smart Broadcasting dalam Pembangunan Media Informasi Digital - Hutagalung, Gabriel Ardi; Aswani, Aprilza; Sinambela, Lamtiur; Harahap, Adhi Surya (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
Nur Azizi Private High School, located in Tanjung Morawa, Deli Serdang Regency, is one of the schools with A accreditation which continues to be committed to improving educational services. However, currently the delivery of information in this school still relies on manual wall magazines, which results in slow distribution of information, lack of interest in reading among students, teachers and staff, as well as dependence on print media. As technology develops, more effective solutions are needed to manage and convey information quickly, directly and accessible anytime and anywhere. Based on the results of discussions with the school, Nur Azizi Private High School needs a digital media that is easy to use, user-friendly, and can speed up the dissemination of information. Therefore, the community service team plans to implement a broadcasting system in the form of a digital website with an auto-reload feature that will be integrated with smart TVs. The implementation of this system is expected to increase the efficiency of delivering information and support the need for faster, more accurate and modern communication at Nur Azizi Private High School. Initial evaluations showed an improvement in the quality of infrastructure and student interest in accessing school information through more modern media.